Jawabanmu

Jawaban paling cerdas!
2014-01-30T15:14:05+07:00
H(x)= ax + b, 
h(5)= 5a + b = 16.....(1)
h(4)= 4a + b = 11.....(2)
pers. 1 dan 2 dieleminasi, maka akan dihasilkan :
a= 5
(1).... 5a +b = 16
                b= 16 - 5a = 16 - (5×5) =16 - 25 = -9

jadi h(-1) = 5 × (-1) + (-9).= -14 
9 4 9
2014-01-30T15:18:34+07:00
H(x) = ax + b
pers 1
h(5) = 5a + b
16  = 5a + b

pers. 2

h(4) = 4a + b
11  = 4a + b

eliminasi :

16  = 5a + b
11  = 4a + b -
5  = a

substitusi :
16  = 5a + b
16  = 5.5 + b
b  = -9

maka persamaan menjadi ;
h(x) = 5x - 9
h(-1) = 5.-1 - 9
h(-1) = -14




3 3 3